Under History's Changing Climate: Anarchism's Romantic Moods. Issue 1 (18th January 2016) - Cohn, Jesse
Abstract: Is anarchism itself a form of what Jerome J. McGann called "romantic ideology, " privileging passion over reason, the affective over the cognitive? An answer is more difficult to give than might be readily apparent. On the one hand, anarchists have defined their political identity against romanticism as the literature of "tender, delicate, distinguished souls, aspiring to heaven, and living on earth as if in spite of themselves (Bakunin)." However, the anarchist tradition does betray a certain romantic genealogy, and anarchists such as Louise Michel, Gustav Landauer, and Rudolf Rocker have often evinced fascination with what Proudhon lambasted as a "literature of decadence." Ultimately, rather than rendering a definitive political judgment on romanticism, anarchists come to enlist elements of its poetry and philosophy to organize affects in response to changing historical conditions.